Comparative Evaluation of Effect of Three Different Calcium Hydroxide Combinations and Triple Antibiotic Paste on Root Dentine Microhardness - An in-Vitro Study - Sokhey, Gulveen; Sharma, Kartik; Singh, Gagandeep; Dhawan , Rajan; Kukreja, Navneet; Bansal, Abhishek (International Journal of Psychosocial Rehabilitation, 2020)
Background: Use of intracanal medicaments (ICM) during root canal treatment procedures have been considered as one of the necessary steps to further decrease the microbial population before obturation. Calcium hydroxide and triple antibiotic paste are the most commonly used intracanal medicaments. Their placement in the root canals exposes the radicular dentine to their action that may cause various surface alterations on it. These surface alterations have reported to decrease the microhardness of the dentine indicating dissolution and degradation. Hence, the goal of this study was to compare the effect of three different calcium hydroxide combinations and triple antibiotic paste on root dentine microhardness. Methodology: Forty extracted human mandibular anterior teeth were taken for the study. After decoronation of the samples, pulp tissue extirpation and biomechanical preparation was done. The prepared teeth were then cut transversely from the middle third of each root such that two uniform root sections were obtained from a single tooth. The obtained root sections were randomly divided into four groups (n=20). Base line microhardness testing was then done. The sections were then placed into petridishes containing calcium hydroxide with glycerine (Group-I), distilled water (Group-II), chlorhexidine gluconate (Group-III) and triple antibiotic paste (Group-IV) respectively. Microhardness testing was repeated in the same manner after 24 hours, 3 days and 7 days. Statistical Analysis: The values obtained after microhardness tests, were statistically analysed using One-way ANOVA test and Post-hoc bonferroni test Results: Overall, the dentin micro-hardness values decreased after treatment with all the tested materials at different interval of time. Triple antibiotic paste group showed maximum decrease in micro- hardness.